IMPLEMENTASI PERHUTANAN SOSIAL DI WILAYAH KERJA PERUM PERHUTANI KPH TELAWA - Henri Supriyanto; Sudarmo Sudarmo; Kristina Setyowati (Jurnal Analisis Kebijakan Kehutanan, 2021)
Policy on Social Forestry of The Ministry of Environment and Forestry is a translation of agrarian reform and President Joko Widodo's Nawacita. Social Forestry with IPHPS program is a specific model implemented in Perhutani working area by providing legal access for forest villagers to manage and utilize forest areas. This research is conducted at Perhutani KPH Telawa, Boyolali Regency. The aim is to analyze the implementation of IPHPS and its impact on society. Data collection is carried out by observation, interviews, and literature studies. Sample is determined by purposive sampling method. The implementation process consists of: (1) application, (2) assistance, (3) financing, (4) coaching and facilitation, (5) monitoring and evaluation. The results of the implementation are: a). Location of IPHPS does not comply with the provisions, which should be empty land for 5 consecutive years, b). The companion is not appropriate in terms of quality and quantity, c). Financing and capital are still independent of farmer groups, d). Coaching and facilitation by the IPHPS Working Group has not been effective yet, e). Monitoring and evaluation was only carried out once, f). Social, economic and ecological impacts are not yet visible.